A comparative study of the morphology of mammalian chordae tendineae of the mitral and tricuspid valves. Issue 2 (26th November 2015) - Hutchison, Jennifer; Rea, Paul
Abstract : It is assumed that the human heart is almost identical to domestic mammalian species, but with limited literature to support this. One such area that has been underinvestigated is that of the subvalvular apparatus level. The authors set out to examine the morphology of the subvalvular apparatus of the mammalian atrioventricular valves through gross dissection and microscopic analysis in a small‐scale pilot study. The authors examined the chordae tendineae of the mitral and tricuspid valves in sheep, pig and bovine hearts, comparing the numbers of each of these structures within and between species. It was found that the number of chordae was up to twice as many for the tricuspid valve compared with the mitral valve. The counts for the chordae on the three valve leaflets of the tricuspid valve, as well as the two mitral valve leaflets, were almost identical between species. However, the chordae attaching onto the posterior papillary muscle were almost double compared with the septal and anterior papillary muscles. Histological analysis demonstrated an abrupt transitional zone. In conclusion, the authors have shown that there is no gross morphological difference between, or within, these species at the subvalvular apparatus level.